Megakaryocyte-specific RhoA deficiency causes macrothrombocytopenia and defective platelet activation in hemostasis and thrombosis - Pleines, Irina; Offermanns, Stefan (Blood, 2012)
Vascular injury initiates rapid platelet activation that is critical for hemostasis, but it also may cause thrombotic diseases, such as myocardial infarction or ischemic stroke. Reorganizations of the platelet cytoskeleton are crucial for platelet shape change and secretion and are thought to involve activation of the small GTPase RhoA. In this study, we analyzed the in vitro and in vivo consequences of megakaryocyte- and platelet-specific RhoA gene deletion in mice. We found a pronounced macrothrombocytopenia in RhoA-deficient mice, with platelet counts of approximately half that of wild-type controls. The mutant cells displayed an altered shape but only a moderately reduced life span. Shape change of RhoA-deficient platelets in response to G13-coupled agonists was abolished, and it was impaired in response to Gq stimulation. Similarly, RhoA was required for efficient secretion of α and dense granules downstream of G13 and Gq. Furthermore, RhoA was essential for integrin-mediated clot retraction but not for actomyosin rearrangements and spreading of activated platelets on fibrinogen. In vivo, RhoA deficiency resulted in markedly prolonged tail bleeding times but also significant protection in different models of arterial thrombosis and in a model of ischemic stroke. Together, these results establish RhoA as an important regulator of platelet function in thrombosis and hemostasis.
Prepublished online as Blood First Edition paper, November 1, 2011
Gesehen am 07.11.2018